An Unusual Case of a Vulva Tumor in an Adolescent: A Case Report and Literature Review - Karaman Ayyildiz, Hayriye Nihan; İlçe, Zekeriya; Tosun, İlkay; Tekkesin, Funda (Acta medica Lituanica, 2026)
Background: We present the case of a 15-year-old adolescent with swelling in the left vulva that was found to have a tumor measuring approximately 20x15 cm in her vulva. Ewing’s sarcoma/primitive neuroectodermal tumors (ES/PNET) are rare and malignant.Materials and Methods: Preoperative magnetic resonance imaging and computed tomography performed to screen for metastasis were negative. The mass was surgically excised in total.Results: Immunohistochemistry showed the mass to be ES/PNET. The patient underwent positron emission tomography-computed tomography which revealed metastasis to inguinal lymph nodes and bone. While under chemotherapy for stage-4 ES/PNET, the patient was found to have lung metastasis. She died due to recurrent chemotherapy complications during treatment.Conclusions: This rare case highlights that significant of early diagnosis and multidisciplinary approach to treatment of ES/PNET cases.
Keywords: adolescent; vulva; primitive neuroectodermal tumors; extraosseous Ewing’s sarcoma